2019
DOI: 10.2340/16501977-2517
|View full text |Cite
|
Sign up to set email alerts
|

Exploring social participation in young adults with cerebral palsy

Abstract: A representative group of young adults with cerebral palsy were studied in order to learn more about social issues, such as living arrangements, employment and relationship status. It was found that, while some young adults were well-established in occupations and relationships, many remained highly dependent on their parental families and their social situation was reduced compared with their peers. Furthermore, lowfunctioning communication level and intellectual disability were the 2 most important risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 25 publications
4
27
0
2
Order By: Relevance
“…Study limitations are primarily the sample size, and the low included proportion of the target population. However, the study sample appear to be representative in terms of sex, distribution of GMFCS‐ER levels, clinical subtypes, and prevalence of important comorbidities such as epilepsy and intellectual disability, as described previously . Accordingly, some important sources of selection bias are likely not present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study limitations are primarily the sample size, and the low included proportion of the target population. However, the study sample appear to be representative in terms of sex, distribution of GMFCS‐ER levels, clinical subtypes, and prevalence of important comorbidities such as epilepsy and intellectual disability, as described previously . Accordingly, some important sources of selection bias are likely not present.…”
Section: Discussionmentioning
confidence: 99%
“…Data collection was performed from 2013 up to 2016. The registry and recruitment process have been described in a previous publication …”
Section: Methodsmentioning
confidence: 99%
“…Logistic binary regression shows that low gross motor function is associated with lower autonomy in leisure (social activities), sexuality, and transportation. Jacobson et al [12] also revealed that for young adults with CP, their functional level has an influence on social participation aspects, such as socialization with friends and experience in intimate relationships (in this study, it was not categorized as being with or without sexual intercourse). Furthermore, Schmid et al [31] found that the autonomy in transportation is lower for those GMFCS levels III–V.…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, much emphasis has now been put on the developmental and healthcare transition process from adolescence to adult life and participation [5,6,7,8,9]. It has been previously reported that young adults with CP participate less in activities, such as housing, paid work, and intimate and sexual relationships than their able-bodied peers [9,10,11], and in terms of finances and activities, many are dependent on parental support [12]. Participation has been defined as involvement in a life situation [13], and for patients with CP, enhancement of participation may lead to a more effective transition to adult life [14,15,16], whereas unemployment, decreased autonomy, and insufficient quality of life may be the consequences of an unsuccessful transition process [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Despite they are nowadays enjoying better health care, new communication technologies, and benefiting from societal attitudes allowing inclusion in all areas of living [ 1 ], they continue to face numerous barriers in their daily lives. Research indicated that amongst others, psychological distress, fragmented social interactions, poor accessibility, discrimination linked to disability, and lack of personal economic independence contribute to limited involvement in life situations [ 2 4 ] that can extend across adulthood. Another area of concern is their ability to access needed resources that may improve autonomy, self-efficacy and health [ 5 ].…”
Section: Introductionmentioning
confidence: 99%